ArchBukhta. Urbanization 2016 - Kazakova, Valentina (project baikal, 2016)
The author shares her impressions of the festival of architectural art “ArchBukhta. Urbanization” organized by the Club of Young Architects. The festival was held in March 2016 in Baikalsk (the Irkutsk region) and concerned the problems of Baikalsk as a monocity. The architectural competition for integration with nature invited the teams to fulfill their concepts related to the topic of the festival: “Impulse for life”. They were invited to reveal the potential for development of Baikalsk, to create a new view of life among citizens, to identify genius loci and to increase the value of the natural factors by artistic means and ecological materials.
Keywords: Baikalsk; monocity; urbanization; new meanings; genius loci